Luminescent metal–organic frameworks (LMOFs) as potential probes for the recognition of cationic water pollutants. Issue 9 (14th April 2020) - Samanta, Partha; Let, Sumanta; Mandal, Writakshi; Dutta, Subhajit; Ghosh, Sujit K.
Abstract : This review aims to provide an overview regarding the development of luminescent metal–organic frameworks (LMOFs) based sensory materials for the detection of cationic inorganic and organic water pollutants. Abstract : Metal–organic frameworks (MOFs) are a unique class of crystalline extended networks with a tuneable architecture. Accordingly, due to their tuneable pores and high surface area, MOFs have gained increasing interest in the last two decades. Luminescent MOF (LMOF)-based sensory materials have provided an excellent platform for the detection of a wide range of toxic, hazardous and biologically important species. Furthermore, the increasing environmental pollution has become an imminent threat to life on Earth. However, the detection of pollutants even at very low levels is still a challenge in the scientific community. Thus, several MOF-based probes have been developed for the sensing of toxic and hazardous species in recent years. Herein, we summarize the MOF-based sensing of cationic organic and inorganic water pollutants based on the recent reports.